Elementary School Communication Transformation: Developing a Parent-Teacher Communication and Information System with the Spiral Method - Denny Jean Cross Sihombing (SEAN Institute, 2023)
Parental involvement is essential in supporting their children's education at the primary school level. Effective collaboration between parents and schools is essential to improve students' motivation, academic achievement, and behavior. In the digital era, communication between parents and teachers has evolved significantly. However, there are still challenges in maintaining effective and regular communication between both parties. This research uses the Spiral development method to address the complexity and dynamics of developing a parent communication and information system in primary schools. The Spiral method was chosen for its flexibility in accommodating unforeseen changes in software development projects. The planning phase involves identifying project objectives, determining the scope of the application, allocating required resources, and planning the development schedule and budget. Risk analysis identifies potential risks such as schedule delays, changing user requirements, and resource limitations. Strategies to address these risks are devised. In the engineering phase, application design, programming, and core testing ensure an intuitive user interface, module implementation, and extensive testing using dummy data. The evaluation phase involved testing the app with 20 teachers and 80 parents, which showed improved communication and user satisfaction. The implementation phase marks the app's official launch, which allows for continuous improvement based on user feedback and evolving communication needs. This research contributes to developing an app that facilitates communication and access to information for all parties involved in primary school education. The app increases parental involvement, addresses communication issues between teachers and students, and facilitates better collaboration. As a result, this research has the potential to positively contribute to improving education and student development in primary schools.